2021
DOI: 10.2320/jinstmet.j2020046
|View full text |Cite
|
Sign up to set email alerts
|

Rapid Evaluation of Hydrogen Embrittlement Resistance for Spot-Welds of High Tensile Strength Steel Sheet by Slow Rate Tensile Shear Test under Hydrogen Charging Conditions

Abstract: Automobile manufacturers are accelerating adoption of spot welding of Advanced High-Strength-Steels (AHSS) sheets to reduce weight of automobile bodies. Rapid evaluation of the hydrogen embrittlement (HE) resistance for the spot-welds of AHSS sheets is required, since it is worried that the HE resistance of the nugget will deteriorate compared to the base metal due to the difference in microstructure caused by rapid cooling and solidification during spot welding. However, evaluation of the HE resistance for th… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1

Citation Types

1
14
0
1

Year Published

2022
2022
2024
2024

Publication Types

Select...
3

Relationship

2
1

Authors

Journals

citations
Cited by 3 publications
(16 citation statements)
references
References 19 publications
1
14
0
1
Order By: Relevance
“…Our samples were martensite steel sheets with a tensile strength class of 1 500 MPa, which were also used in the previous study. 19) Tables 1 and 2 show the mechanical properties and chemical compositions of these materials, respectively.…”
Section: Methodsmentioning
confidence: 99%
See 2 more Smart Citations
“…Our samples were martensite steel sheets with a tensile strength class of 1 500 MPa, which were also used in the previous study. 19) Tables 1 and 2 show the mechanical properties and chemical compositions of these materials, respectively.…”
Section: Methodsmentioning
confidence: 99%
“…However, few studies have assessed the hydrogen embrittlement of spot welds in high-tensile-strength steel sheets and the mechanism of hydrogen embrittlement. [17][18][19] In a previous study, 19) we used the tensile shear test, which is used to evaluate the strength of spot welds, to assess the hydrogen embrittlement of spot welds in high-tensile-strength steel sheets and reported the results of introducing diffusible hydrogen under a cathodic charge. The results showed that as the diffusible hydrogen content of the test specimens increased, the tensile shear strength decreased.…”
Section: Introductionmentioning
confidence: 99%
See 1 more Smart Citation
“…水素脆化感受性が増大するため 3) ,スポット溶接部におい ても水素脆化の懸念がある。 水素脆化メカニズム解明に向けた材料試験や高張力鋼板 の活用のための水素脆化評価法として多くの先行研究 [4][5][6][7][8][9][10][11][12][13][14][15] が実施されている。U 曲げ試験 [4][5][6][7] では,板材の加工ひず みの影響を考慮した評価法であり,しばしば実施されてい る。また,材料の水素脆化評価としては,高力ボルトの評 価 8) と同様に,4 点曲げ 9,10) や 3 種の引張試験;低ひずみ速 度 法(SSRT:Slow Strain Rate Technique) 11,12) ,通常の引張 試 験(CSRT:Conventional Strain Rate Technique) 11,13) ,およ び定荷重試験(CLT:Constant Load Test) 11,14,15) が実施され ている。各試験法については,メリット,デメリットがあ り,鋼板を評価するための最適な試験法についての結論は 出ていないが,各種試験法による評価結果の差異 11) ,拡散 性水素量や転位と水素の集積など水素脆化を支配する因 子 16) については明らかになりつつある。一方,高張力鋼板 をスポット溶接したときのスポット溶接部の水素脆化評価 や水素脆化挙動に関する研究は少ない [17][18][19] 。著者ら 19)…”
unclassified
“…3. Diffusible hydrogen content of spot welds after tensileshear fatigue tests and slow rate tensile-shear tests(S-TST)19) under different hydrogen charging conditions.…”
mentioning
confidence: 99%